Perspektif Kognitif Keterlibatan Perspektif Teori Kognitif Pada Penggunaan Model Pembelajaran Inkuiri Dalam Mata Pelajaran PAI - Nurul Isma Rafika (Jurnal Al-Fatih, 2024)
The main issue identified in this study is the low level of interpersonal intelligence among children at RA An-Nur Gunting Saga, as evidenced by their limited ability to interact and play with peers. This condition indicates the need for an appropriate learning strategy, particularly through the use of the role-playing method to enhance children’s social abilities. The purpose of this research is to determine the improvement of children’s interpersonal intelligence through the implementation of role-playing activities. This Classroom Action Research (CAR) was conducted in two cycles consisting of planning, action implementation, observation, and reflection. Data were collected through observations and checklists to assess children’s interpersonal skills. The focus of the study includes an overview of the interaction abilities of children aged 5–6 years prior to the application of the role-playing method and the extent of improvement that occurred afterward. The findings show that the role-playing method significantly enhances children’s interpersonal abilities in accordance with the established developmental indicators. In the first cycle, 8 out of 13 children achieved mastery (61%), while 5 children had not yet achieved it (39%). In the second cycle, the number of children who achieved mastery increased to 11 (85%), with only 2 children remaining below the mastery level (15%). Based on these findings, it can be concluded that the role-playing method is effective in improving the interpersonal intelligence of children at RA An-Nur Gunting Saga.